Time Processing and Motor Control in Movement Disorders - Avanzino, Laura; Pelosin, Elisa; Vicario, Carmelo M.; Lagravinese, Giovanna; Abbruzzese, Giovanni; Martino, Davide (Frontiers in Human Neuroscience, 2016)
The subjective representation of “time” is critical for cognitive tasks but also for several motor activities. The neural network supporting motor timing comprises: lateral cerebellum, basal ganglia, sensorimotor and prefrontal cortical areas. Basal ganglia and associated cortical areas act as a hypothetical “internal clock” that beats the rhythm when the movement is internally generated. When timing information is processed to make predictions on the outcome of a subjective or externally perceived motor act, cerebellar processing and outflow pathways appear to be primarily involved. Clinical and experimental evidence on time processing and motor control points to a dysfunction of the neural networks involving basal ganglia and cerebellum in movement disorders. In some cases, temporal processing deficits could directly contribute to core motor features of the movement disorder, as in the case of bradykinesia in Parkinson’s disease. For other movement disorders, the relationship between abnormal time processing and motor performance is less obvious and requires further investigation, as in the reduced accuracy in predicting the temporal outcome of a motor act in dystonia. We aim to review the literature on time processing and motor control in Parkinson’s disease, dystonia, Huntington’s disease, and Tourette syndrome, integrating the available findings with current pathophysiological models; we will highlight the areas in which future explorations are warranted, as well as the aspects of time processing in motor control that present translational aspects in future rehabilitation strategies.